Eelam Poetry and the beginning of Penmozhi - M, Padma Priya (International Research Journal of Tamil, 2022)
Writing is the key to changing society. All those who have been excluded as unclean are exposed today. Women’s liberation is not about leaving the door, it is only possible in poetry to feel the expansion of the boundary to break the lock of the language. On the one hand, the achievement of the female language, the thrill of womanhood. No, this is an ’alternative politics’, on the one hand. However, the purpose of feminist poetry is to face the future through language. The restrictions imposed by society on the female body, such as the summary laws of the outer space, etc. The illusions that invented later traditions based on traditional examples of female image (for example, the female image of Sita, Kannagi, Nalaini, etc., recorded the female tradition. Mother Karaikal was conducted with a bone towards Kayil, and the mother’s consciousness was dried with devotional dye.) The female language is the expression of the imposition through the way. The study indicates that the impact of the female language being constructed by tamil women poets Malathi Maitri, Lena Manimegalai, Kuttilathi and Sugirtha Rani followed the beginning of Eelam.